The Radical Party in the Kirk, 1637–45 - Stevenson, David (The journal of ecclesiastical history, 1974)
In the Scottish General Assembly of 1638 the Covenanters, openly defying Charles I, reformed the kirk to remove what they saw as its corruptions. Bishops and the Court of High Commission were abolished. The Five Articles of Perth (regulating certain points of worship), the 1636 Book of Canons and the hated Prayer Book of 1637 were all condemned.